Spirituality and rationality in modern culture - Pischykov, Volodymyr; Kholin, Mykhailo (Actual Problems of Mind, 2017)
The article raises the question of the status of rationality and spirituality in modern culture. The orientation of rationality to situationality and utilitarian pragmatism leads to the contradiction of rationality and spirituality. The rejection of the highest, absolute, universal spiritual values that gave individual (and social) being integrity, change the person himself, turning him into a utilitarian individual, driven by uncritical-pragmatic rationality